2006
DOI: 10.1111/j.1440-1630.2006.00615.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of recruitment and retention issues for occupational therapists working clinically in mental health

Abstract: Recruitment and retention strategies are required to retain occupational therapists in clinical mental health positions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 17 publications
0
40
0
Order By: Relevance
“…Results from this study also allow for the exploration of the influence of ‘generic working’ on work wellbeing. Existing literature suggests ‘generic working’ may negatively impact the wellbeing of occupational therapists in mental health, especially for those working in community‐based settings (Ashby et al ., ; Brown et al ., ; Ceramidas, ; Hayes et al ., ). This study provided a range of data to further explore this issue.…”
Section: Discussionmentioning
confidence: 97%
“…Results from this study also allow for the exploration of the influence of ‘generic working’ on work wellbeing. Existing literature suggests ‘generic working’ may negatively impact the wellbeing of occupational therapists in mental health, especially for those working in community‐based settings (Ashby et al ., ; Brown et al ., ; Ceramidas, ; Hayes et al ., ). This study provided a range of data to further explore this issue.…”
Section: Discussionmentioning
confidence: 97%
“…These competing pressures could increase exhaustion and this was articulated by participants in interviews: going ‘above and beyond’ their expected role to provide occupational therapy interventions. This finding is also consistent with other literature exploring occupational therapy roles in mental health settings where the pressure to provide ‘generalist’ interventions as well as occupational therapy‐specific interventions was identified as a source of stress (e.g., Ceramidas, ; Hayes et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Access to professional supports and supervision has been highlighted as important for supporting professional identity and job satisfaction for occupational therapists in mental health (Ashby et al ., ; Hayes et al ., ; Scanlan et al ., ). The importance of supervision was also highlighted by participants in the current study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the United Kingdom, it has been observed that recruitment and retention of occupational therapists in mental health settings is difficult (Edwards & Burnard, 2003;Hunter & Nicol, 2002). Similar problems have been reported in Australia (Hayes, Bull, Hargreaves, & Shakespeare, 2006). If many occupational therapists are choosing not to go into mental health practice, and some do not recognize the usefulness of psychosocial skills in their interventions, does it mean that we have failed to respond to Mary Reilly's (1962) call to reclaim the foundational principles of the profession?…”
mentioning
confidence: 97%